Nature and Skills of Effective Leadership for The Success of Literacy Programs in Elementary Schools - Wibowo, Udik Budi; Sayekti, Octavian Muning; Dewanti, Septinda Rima (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
The School Literacy Movement program launched by the government has not yet been to be implemented optimally. One of the factors that influence it is related to the leader